Screening for Asymptomatic Bacteriuria in Adults - Maryati, Maryati; Sugiarto, Sugiarto (International Medical Journal Corp. Ltd, 2024)
Background: The literature surrounding asymptomatic bacteriuria (ASB) has evolved significantly over the past decade, reflecting a complex interplay of epidemiological insights, clinical management, and evolving guidelines. Literature Review: The foundational study by (Olowe et al., 2013) establishes the prevalence of ASB among elderly and middle-aged individuals in rural Nigeria, identifying significant bacteriuria as a pressing concern, particularly in vulnerable populations. This study highlights the need for targeted screening and raises questions about the treatment benefits for these groups. Further exploration by (Prabha, 2016) focuses on antenatal women, emphasizing the increased risk of ASB during pregnancy and the potential complications arising from untreated cases. The identification of urine culture as the gold standard for screening is crucial, reinforcing the need for effective diagnostic strategies in this demographic. Conclusion: In conclusion, the literature collectively underscores the necessity for targeted screening and treatment approaches for ASB, particularly for at-risk populations such as pregnant women and the elderly. The consensus against routine treatment in asymptomatic individuals highlights the importance of evidence-based guidelines in clinical practice. Future research should focus on developing innovative screening methods and clarifying the management of ASB in various populations to enhance patient care and outcomes.